2019
DOI: 10.3762/bjoc.15.135
|View full text |Cite
|
Sign up to set email alerts
|

Anomeric sugar boronic acid analogues as potential agents for boron neutron capture therapy

Abstract: After the development of accelerators as neutron source, the access to new suitable agents for boron neutron capture therapy (BNCT) became a major need. Among many others, sugar boronic acids have recently attracted attention as boron carriers. Herein we report the synthesis and preliminary biological studies of two new sugar analogues containing a boronic acid at the anomeric position. The analogues were obtained by hydroboration of proper open-chain terminal alkenes that, after quenching with water, spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…These include boron‐containing porphyrins, polyamines, amino acids, nucleosides, peptides, sugars, monoclonal antibodies, liposomes, nanoparticles, boron cluster compounds and co‐polymers . Recently, boronic acid derivatives of monosaccharides have been proposed . Simple sugars represent an interesting tool in delivering boron to malignant cells, exploiting the concept of the Warburg effect.…”
Section: Introductionmentioning
confidence: 99%
“…These include boron‐containing porphyrins, polyamines, amino acids, nucleosides, peptides, sugars, monoclonal antibodies, liposomes, nanoparticles, boron cluster compounds and co‐polymers . Recently, boronic acid derivatives of monosaccharides have been proposed . Simple sugars represent an interesting tool in delivering boron to malignant cells, exploiting the concept of the Warburg effect.…”
Section: Introductionmentioning
confidence: 99%
“…These include vaborbactam, a β-lactamase inhibitor, tavaborole, a leucyl-tRNA synthetase inhibitor, and crisaborole, a phosphodiesterase-4 inhibitor. Several other borocycles acting as β-lactamase inhibitors were identified [16][17][18][19], and Imperio et al reported cyclic boronic acid sugar analogues which could function as potential agents in boron neutron capture therapy [20]. Nevertheless, to the best of our knowledge, no cyclic boronates were investigated as iCP inhibitors until the present work.…”
Section: Introductionmentioning
confidence: 95%
“…A further report on boronic acid analogs of monosaccharides describes the synthesis of the hexose analogs 30 and 34 [37] (Scheme 5) bearing the boron atom at the anomeric position. As already reported for other sugar boronic acids, compound 30 gave a slow elimination reaction to the alkenol 31, while 34 was shown to be very stable.…”
Section: Sugar-containing Boronic Acidsmentioning
confidence: 99%
“…The stability of 27e can be attributed to the rigidity of the structure, which could hamper the β-elimination reaction, which probably requires a periplanar conformation. To summarize, it appears from literature data that β-hydroxyboronic A further report on boronic acid analogs of monosaccharides describes the synthesis of the hexose analogs 30 and 34 [37] (Scheme 5) bearing the boron atom at the anomeric position. As already reported for other sugar boronic acids, compound 30 gave a slow elimination reaction to the alkenol 31, while 34 was shown to be very stable.…”
Section: Sugar-containing Boronic Acidsmentioning
confidence: 99%